Using local Iraqi Bacillus isolate to reduce water salinity - Humudat, Yasmen Raad; Al-Naseri, Saadi Kadhim; Kadhim, Suadad Awad (Iraqi Journal of Science, 2018)
Microbial desalination cell (MDC) has been created for expelling water saltiness, power generation, and wastewater administration. The MDC comprised of three chambers (anode, center desalination, and cathode).Were tested ability of type locally isolated bacteria Bacillus spp.in produce electricity to water desalination. In recent study results showed that a remove where the salinity recorded 4000 ppm at room temperature at the voltages of 0.6 volts and less salinity at room temperature at 0.2 volts was 200 ppm. Recent results highlight the need to reduce time for reduce salinity decreased from 3500 ppm to 500 ppm the eleventh day at a voltage of 0.5 volts that depended on type of substrate.